Relationship of Religion and Culture - Surya Hadi Darma; Dadang Kahmad; Afif Muhammad; Yusuf Wibisono (International Journal of Nusantara Islam, 2021)
This research focuses on issues of religious, cultural and political conflicts and the integration of Ulama and Umara in Purwakarta which intersect with the political dimensions ahead of the Regional Head Election. The specific focus is on the evaluation of religion over culture and turns into a strategic issue played by interest groups. This research is a type of field research research using a qualitative dialectical phenomenological approach as the method. The collection of data and information was carried out by means of observation techniques. The findings of this study include the first, the religious and cultural relations in Purwakarta due to the perspective of the FPI, KUI and FUI mass organizations in assessing that the preservation of Sundanese culture in Purwakarta is contrary to Islamic teachings. second, the form of conflict between Ulama and Umara begins with the case of "the flute and the Koran, the making of puppet figures, the Hideung Bodas (Black and White) Festival of the Tumpeng Parade, the Bebegig Parade, to the confrontation of Sampurasun vs campurracun, and is closely related to political issues. and religious doctrine and understanding of Sundanese culture. But then it is processed into a religious issue and utilized by interest groups.Third, efforts to integrate ulama and Umara are carried out by holding a Cultural and Religious Workshop, establishing communication and compromising on the conflicts that occur.